GAMBARAN KEKERASAN YANG DIALAMI PADA ANAK JALANAN DI KOTA PEKANBARU - maulanaprasetyo maulana (Jurnal Medika Hutama, 2021)
Street children are individuals time on the road. Street children are very vulnerable to various violent behaviors. this study aims to find out the description of violence experienced by street children in Pekanbaru City with a sample of 94 responden. Sampling was done by purposive sampling technique and data collection using questionnaires and data analysis using univariate analysis of each aspect a the result of physical hardness drawn his clothes as much as 85 (90,4%), beaten 83 (88,3%), Kicked 80 (85,1%) mayority occurred in boy. Psyco;ogical violence such as ridicule 82 (87,2%), scolded as much as 73 (77,7%), barked as much 69 (73,4%) majority happened to street childreen of male gender. sexual violence of boys more often get noncontact sexual violence behavior as shown pornographich images as much as 53 (56,4%) are invited to watch porn vidio as much 48 (51,1%). However, women are more susceptible to direct sexual violence such as being asked to touch the genitals of other people as much as 28 (29,8%), to be touched by other people as much as 23 (24,5%). Violence neglet as forced to woek by the parents as much as 20 (21, 3%), felt not paid attention by parents as much as 20 (21,1%). It can be concluded that boys experience violence more often than girls. Kata Kunci : Anak jalanan, Kekerasan fisik, Kekerasan psikis, Kekerasan seksual, Kekerasan penelantaran